Temperature in overwintering honey bee colonies reveals brood status and predicts colony mortality - Etienne Minaud; François Rebaudo; Giulia Mainardi; Philippos Vardakas; Fani Hatjina; Ingolf Steffan-Dewenter; Fabrice Requier (Ecological Indicators)
Winter losses in honey bee colonies, Apis mellifera, raise concerns both for their critical role in crop pollination and for the sustainability of beekeeping. Beekeepers struggle to limit losses due to a lack of indicators to measure colony health and predict mortality in winter under field conditions. Due to the critical role of social thermoregulation for winter colony survival and brood production, this study aims to assess whether monitoring nest temperature during the winter may provide indicators of the state of health and survival of honey bee colonies. Under field conditions, we monitored the nest temperature of 31 hives distributed along a thermal gradient spanning over different European climates (including France, Germany, and Greece) over the winter 2022–2023. We installed 1,083 temperature sensors at multiple points inside the hives, with an average of 35 ± 1.1 sensors per hive (mean ± SD). We collected a total of 26,322,085 temperature data measurements for which we computed the time series of minimum, median, maximum temperature, and thermal amplitude. We found that the thermal amplitude within the nest is an indicator of colony health, effectively distinguishing between surviving and dying colonies with an accuracy of 96.8 %. Moreover, we found that nest temperature enables the detection of collapsing phases with an accuracy of 83.9 % and up to one month before the death of the colony. Finally, we showed that monitoring nest temperature in winter can help detect brood presence and size, an important health indicator for beekeeping. We suggest that monitoring nest temperature could represent a relevant field indicator of honey bee colony health for understanding the success or failure of overwintering. This indicator could help beekeepers anticipate colony mortalities to limit the winter colony losses observed worldwide.